Motivation, learning strategies and performance among business undergraduates at university colleges in Sweden - Bengtsson, Elias; Teleman, Britta (Business, Management and Economics Engineering, 2019)
Purpose – This paper brings new material to the understanding of interlinkages between motivation, learning and performance in academic contexts. By investigating these interlinkages in a new context – students of business and management at a Swedish university college – it seeks to answer the following research questions: How do students’ degree and type of motivation relate to their learning strategies?; how do students’ degree and type of motivation and learning strategies relate to their academic success?; and how do student characteristics in terms of experience and gender influence the nature and strength of these relationships? Research methodology – The data used in this paper is based on student surveys and a centralised system of reporting and archiving academic results. The latter contains information on the academic performance of individual students, whereas the surveys gathered information on the students’ background characteristics (experience and gender), their motivation for pursuing academic studies and their learning strategies. The difference in proportion tests and OLS regressions were then applied to investigate differences between student groups and relationships between the different variables. Findings – The findings reveal that business students are more extrinsically than intrinsically motivated; that deep learning approaches lead to higher grades for particular examination forms, and that female students are typically more intrinsically motivated, engage more in deep learning approaches and perform better than their male counterparts. Practical implications – The findings suggest that practitioners in higher education involved with the business and/or university college students have good reasons to stimulate motivation generally, and intrinsic motivation in particular. However, this must be accompanied by examination forms that promote deep learning. Originality/Value – In contrast to most research, this paper focuses on the interlinkages between motivation, learning and performance among business students in a university college setting. This contrasts most research on this topic which tends to be focused on university students, particularly in the US, in other fields of study or accounting. Moreover, this paper also takes student characteristics into account and uses a variety of measures to operationalise academic performance.